Soroperfil e soroprevalência para Lawsonia intracellularis em rebanhos suínos do estado de Minas Gerais - Talita Pilar Resende (2015)
Lawsonia intracellularis is the etiologic agent of proliferative enteropathy, which causes diarrhea in several animal species including swine. To determine the serological profile and the seroprevalence of anti-L. intracellularis antibodies in swine herds of intensive production of Minas Gerais, 30 farrow to finish herds were chosen by sampling in multiple stages and selection for convenience. In these herds 20 blood samples were obtained from animals of different stages of the production cycle (maternity, nursery, rearing, termination and arrays), and subsequently analyzed by immunoperoxidase in monolayer assay. The overall prevalence in Minas Gerais was 34.66% and there was no statistical difference among the sampled mesoregions, with seroprevalence rates ranging between 32.06% and 37.66%. Finishing pigs were the most prevalent among the sampled categories. Only the frequency of animal introduction on the property was a risk factor related to positive status of the herds. The anti-L. intracellularis antibodies were present in all investigated herds of Minas Gerais, indicating a spread of the agent in the state. The predominant seroprofile was in line with the dynamics of infection previously observed in pig herds in other countries with similar antibiotics use.